Retinoic acid liposome-hydrogel: preparation, penetration through mouse skin and induction of F9 mouse teratocarcinoma stem cells differentiation - Hongmei Xia; Yongfeng Cheng; Yinxiang Xu; Zhiqing Cheng (Universidade de São Paulo, 2015)
Retinoic acid (RA), a metabolite of retinol, is one of the most biologically active forms of retinoid and plays vital roles in embryonic development and in the regulation of cell proliferation and differentiation. Knowing that liposomes simulate cell membranes and that hydrogel is an ideal delivery vehicle for topical medicine, liposome-hydrogel is a novel preparation that has synergistic advantages over each component separately. Our objective was to investigate the characteristics of RA liposome-hydrogel. For quality control of the RA-loaded liposomes, we measured their morphology, particle size, Zeta-potential, and entrapment efficiency. Then we determined the viscosity of RA liposome-hydrogel. Next, the diffusion through mouse skin was explored, followed by investigation of the mRNA expression levels of Ker18, REX1, and α-FP using Q-PCR. The results showed that RA liposome-hydrogel penetrates the mouse skin effectively. The permeation rates were: Qn (%) of RA liposome-hydrogel < Qn(%) of RA-loaded liposome < Qn (%) of RA. The mRNA expression levels were dose-dependent and the effective dose decreased between vehicles due to their different release rates. F9 mouse teratocarcinoma stem cells were an ideal model to explore the mechanism of RA liposome-hydrogel in stem cell differentiation.